Enhancing Elementary Students’ Numeracy Skills through Ethnomathematics in Geometry Learning: A Systematic Literature Review - Rahayu, Ida; Salim, Herli; Munandar, Arif (International Conference on Elementary Education, 2025)
The abstract should concisely summarize the research problem, objectives, methodology, key findings, and conclusions. It must not contain citations, references, or quotes. The abstract should be clear and self-contained, giving readers a quick overview of the entire study. The length of the abstract should be between 150-200 words, ensuring it remains informative without being too detailed. The formatting requirements include using Helvetica 9pt font, with single line spacing to maintain readability and professional appearance. All essential elements, such as the study’s problem, goals, methods, results, and final conclusions, must be clearly presented.